Purity and identity in ancient Judaism: from the temple to the Mishnah - Fursṭenberg, Yaʾir (Olamot Series in the Humanities and Social Sciences, 2023)
The concern for purity was the cornerstone of the religious culture of ancient Judaism. Purity and Identity in Ancient Judaism explores how this concern shaped the worldview of Jews during the Second Temple period as well as their daily practices and social relations. It examines how different groups offered competing visions and methods for living a life of purity, which embodied a promise for personal and cosmic salvation and at the same time determined the degree of sectarian separation. Purity and Identity in Ancient Judaism offers a comprehensive description of the world of purity among the Jews of the Second Temple period in general and within the tradition of the Pharisees in particular. Yair Furstenberg explores the language of purity that provided Jews in antiquity a powerful tool for organizing legal, social, and ideological boundaries, and its study is therefore pertinent for understanding the powers that shaped the varieties of Second Temple Judaism and their later offshoots: Early Christianity and Rabbinic Judaism. Purity and Identity in Ancient Judaism offers new methods for carefully integrating the New Testament, Qumran literature, and early rabbinic sources into a comprehensive history of purity laws from the world of the Second Temple and the Pharisees to the later rabbinic movement, allowing the reader to trace the emergence of new religious sensibilities within changing social and cultic circumstances